Emergency contraception: an untapped resource among sexually active college students in Osogbo metropolis, Nigeria - Asekun-Olarinmoye EO; Adebimpe WO; Adeomi AA; Olugbenga-Bello AI (Dove Medical Press, 2013)
Esther O Asekun-Olarinmoye,1 Wasiu O Adebimpe,1 Adeleye A Adeomi,2 Adenike I Olugbenga-Bello2 1Department of Community Medicine, Osun State University, Osogbo, Nigeria; 2Department of Community Medicine, Ladoke Akintola University of Technology Teaching Hospital, Ogbomoso, Nigeria Introduction: Unwanted pregnancies and unsafe abortions result in the death of thousands of women, while millions suffer from permanent or temporary disabilities, problems that the use of emergency contraception can ameliorate. This study was therefore carried out to assess the knowledge, attitude, and practice of emergency contraception (EC) among college students in Osogbo metropolis. Materials and methods: This descriptive cross-sectional study was carried out among 594 college students in Osogbo metropolis in Osun State, Nigeria, using pretested, semistructured questionnaires. Respondents were selected by multistage sampling. Data were analyzed using SPSS software, version 15. Results: The mean age of the respondents was 23.45 ± 3.63 years. Mean age at first sexual exposure was 19.34 ± 4.34 years. Awareness about EC was fairly high among the respondents, (403, 67.8%), with categorized scoring of outcome variables showing that 60.8% of respondents had good general knowledge and only 27.9% had a positive attitude towards EC. However, only 66 (29.9%) of the sexually active respondents had ever used EC before the study, while 26 (21.5%) of the 121 sexually active female respondents admitted to having had an abortion. Bivariate analysis revealed that respondents’ knowledge of, and attitude towards, EC were significantly related to age (P < 0.00000001), respondents’ course of study (P < 0.00000001), and their level in college (P = 0.0000002), while the use of EC among the sexually active students was significantly related to respondents’ knowledge of EC (P = 0.017). Conclusion: Fairly high awareness, good general but poor comprehensive knowledge, negative attitudes, and poor use characterized the practice of EC among our study population. There is therefore a need for health-education initiatives about EC, addressing specific areas of poor knowledge and clarification of common misconceptions. Keywords: knowledge, attitude, practice, college students, emergency contraception